História de vida na pesquisa com adultos com deficiência: algumas reflexões - Rogério Drago; Camila Reis do Santos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
Understanding that the human being produces history and culture at the same time it is invaded by history and culture of other beings with which it comes in contact throughout their lives, this text discusses the methodology of life history for research adults who have disabilities, pervasive developmental disorders or high skills giftedness, acknowledging them as individuals who have a voice and from their narratives, can contribute to their subjectivities and identities are recognized. In this sense, it is a theoretical study which shows the characteristics of the method of life history, its importance for educational research, its procedures and its value in the rescue of the identity and subjectivity of adults with disabilities, disorders global development or high abilities / giftedness.